Macroprudential stress test of the euro area banking system - Katarzyna Budnik; Mirco Balatti Mozzanica; Ivan Dimitrov; Johannes Groß; Ib Hansen; Michael Kleemann; Francesco Sanna; Andrei Sarychev; Nadežda Siņenko; Matjaz Volk; Giovanni di Iasio (European Central Bank (ECB), 2019)
This paper presents an approach to a macroprudential stress test for the euro area banking system, comprising the 91 largest euro area credit institutions across 19 countries. The approach involves modelling banks'reactions to changing economic conditions. It also examines the effects of adverse scenarios on economies and the financial system as a whole by acknowledging a broad set of interactions and interdependencies between banks, other market participants, and the real economy. Our results highlight the importance of the starting level of bank capital, bank asset quality, and banks' adjustments for the propagation of shocks to the financial sector and real economy.
Keywords: E37; E58; G21; G28; 330; macro stress test; macroprudential policy; banking sector deleveraging; real-financial feedback mechanism